ANALYSIS OF THE EFFECTS OF WIND SPEED AND CONIDIAL DENSITY ON LEAF RUST DISEASE (PHAKOPSORA PACHYRHIZI) IN IMMATURE OIL PALM PLANTATION AREAS - Kania Yustika Pakpahan; Guntoro; Nurliana (RADJA PUBLIKA, 2026)
This study aimed to analyze the effects of wind speed and conidial density on edamame leaf rust disease caused by Phakopsora pachyrhizi in immature oil palm plantation areas. The research was conducted at the Oil Palm Practice Farm of the Indonesian Oil Palm Institute of Technology, Deli Serdang, North Sumatra, through wind speed measurement, conidial observation using a spore trap, and disease intensity assessment. The data were analyzed using multiple linear regression with SPSS through classical assumption tests, t-test, F-test, and the coefficient of determination. The results showed that the regression model met the normality assumption, had no multicollinearity, and showed no indication of heteroscedasticity. Partially, wind speed did not have a significant effect on disease intensity (p = 0.437), whereas the number of conidia had a significant effect (p < 0.001). Simultaneously, both variables had a significant effect on disease intensity (F = 442.472; p < 0.001), with an R Square value of 0.955. These findings indicate that conidial density is an important indicator in the development of edamame leaf rust disease.